Reparação de danos pelo incapaz (artigo 928 do Código Civil) - Frascino, Christiane Macarron (2008)
The legal system absorbs the social facts and transforms itself according to the interests, desires, ethic and moral values which predominate in the society that is worried with balance, justice and its social aspect. The unfair payment of indemnification is denied by the individuals and those factors determine that the victim shall not stay without any sort of reparation, even in case of damage caused by a disabled, but financially able to pay for at least part of such indemnification. Thus, based on equity, it was introduced in our legal system that The disabled is liable for the damage that he may cause, if the ones for him responsible are not obliged to do so or do not possess the means for that. (Article 928 from the Civil Code of 2002 caput). However, as it deals with disabled people, the liability of indemnifying is subsidiary to the one of his legal representative or responsible person and must attend the concepts from the unique paragraph from the article 928: The indemnification predicted in this article, that shall be equitable, will not be valid if it removes from the disabled person his basic needs or even from the ones dependent on him. The current Civil Code followed the world tendency of making the victim in dene, whenever possible, based on the sociality, human being dignity, justice feeling, and when it comes to the disabled person, especially, on equity, that became the main point of the law enforcer. Such are the requirements for the assets of the disabled to answer for the damages caused by him: (i) the illegal act performed by the disabled would make a legally capable person responsible, in a similar situation; (ii) causation between fact and damage, injury (iii) that his responsible does not have the legal duty to answer for the damage or cannot afford the indemnification; (iv) fixation of equity as it is impossible to compromise his survival or his dependent s basic needs. Consequently, it tends to promote the social life of the disabled, granting them guarantees of constitutional rights and integration, and to the society a better result concerning the indemnification of possible damage caused by them. Although the victim shall stay with no due reparation if the responsible person does not have the legal duty for that or, no means to support such indemnification, and the disabled could not afford any indemnification without losing his basic needs for survival or of his dependents